Changes in clinical outcomes for community‐dwelling older people exposed to incident chronic polypharmacy: a comparison between 2001 and 2009. Issue 2 (21st December 2015) - Franchi, Carlotta; Marcucci, Maura; Mannucci, Pier Mannuccio; Tettamanti, Mauro; Pasina, Luca; Fortino, Ida; Bortolotti, Angela; Merlino, Luca; Nobili, Alessandro
Abstract: Purpose: The purpose of this study is to explore the effect of incident chronic polypharmacy on 1‐year hospitalization, institutionalization, and mortality among older people and to evaluate whether or not the effect differed according to index year (2001 or 2009), sex, and age. Methods: Data were obtained from the administrative database of the Lombardy region (Northern Italy). We compared community‐dwelling elderly people with an incident exposure to chronic polypharmacy (five or more drugs during 1 month for at least 6 months in 1 year) in either index year (2001 and 2009) with not exposed elderly people in the same years. Multivariable logistic (institutionalization) and Cox (hospitalization and death) were performed including year, sex, age classes, and number of drugs as covariates and their respective interaction terms by chronic polypharmacy. Results: We analyzed 1, 800, 257 elderly subjects in 2001 and 1, 567, 575 in 2009, with a prevalence of chronic polypharmacy of 1.46% and 2.86%, respectively. Overall, 1‐year hospitalization, institutionalization, and mortality rates were lower in 2009 than in 2001. Chronic polypharmacy was significantly associated with the outcomes in multivariable analyses: hazard or odds ratios 1.16 (95% confidence interval 1.14–1.17) for hospitalization, 1.21 (1.12–1.30) for institutionalization, and 1.11 (1.08–1.14) for death. There was no consistent effect modification by index year or sex, whereas chronic polypharmacy was no longer a risk factor for adverse outcomes among those older than 85 years ( p < 0.0001 for interaction). Conclusions: Incident chronic polypharmacy remained an independent predictor of adverse outcomes among community‐dwelling elderly people, despite a reduction over time of 1‐year hospitalization, institutionalization, and mortality rates. Copyright © 2015 John Wiley & Sons, Ltd.